1983
DOI: 10.1002/joc.3370030107
|View full text |Cite
|
Sign up to set email alerts
|

Modelling climate and the nature of climate models: A review

Abstract: A new structural framework for climate models is presented. Four basic model types are discussed: general circulation models, energy balance models, one dimensional radiative convective models and two dimensional zonally averaged dynamical models. The fundamental importance of three primary processes in the climate system-radiation, dynamics and surface processes-is underlined and the degree to which each of these mechanisms is incorporated in each model is highlighted.KEY WORDS Climate models General circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…A brief introduction to general circulation models An introduction to the general circulation models (GCMs) used in climate studies can be found in Shine and Henderson-Sellers (1983). A more technical but well-explained account of atmospheric dynamics and the basic equations used in numerical climate and weather forecasting models can be found in Atkinson (19811, a book designed for the general scientific reader.…”
Section: Using a General Circulation Model O F The Atmosphere To Simumentioning
confidence: 99%
“…A brief introduction to general circulation models An introduction to the general circulation models (GCMs) used in climate studies can be found in Shine and Henderson-Sellers (1983). A more technical but well-explained account of atmospheric dynamics and the basic equations used in numerical climate and weather forecasting models can be found in Atkinson (19811, a book designed for the general scientific reader.…”
Section: Using a General Circulation Model O F The Atmosphere To Simumentioning
confidence: 99%
“…One such laudable undertaking, among many others, was that of the US NAS which was recently published in a voluminous report (CDAC, 1983). Some of the major uncertainties which affect the reliability of output from GCMs include physical processes and boundary conditions, regional climate changes and transient changes due to the combined greenhouse gases (Liss and Crane,1983 ;Manabe, 1983;Shine and Henderson-Sellers, 1983;Rind and Lebedeff, 1984).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The recognition that different aspects of the climate system demand different types of simplification has led to the development of a wide variety of climate model types (e.g. Shine and Henderson-Sellers, 1983;Henderson-Sellers and McGuffie, 1999). In selecting the type of climate model to be employed for a particular simulation task, it is necessary to balance socio-economic and scientific understanding and outcome demands against available computational capability, and review all three in the context of the data with which parameterizations and initializations will be established (cf.…”
Section: Complexity 6ersus Conceptualizationmentioning
confidence: 99%